Consumption Patterns and Utilisation of Provisioning and Cultural Ecosystem Services in Lambaréné, Gabon - Biname Djeph Wylphene Koumba; Gbadegesin Adeniyi; Okanga-Guay Marjolaine (Journal of Landscape Ecology, 2025)
Ecosystem Services are crucial for human well-being and food security, with consequences for socioeconomic wellbeing. To ensure long-term usage and preservation of Ecosystem Services, they must be valued. The current study examines the dependence on provisioning and cultural Ecosystem Services in Lambaréné, Gabon, using a quantitative method approach, data were collected from 405 households, employing both descriptive and inferential statistic through questionnaires. Results show high reliance on provisioning services, with significant dependencies on fish and firewood for sustenance and energy, and strong cultural values attached to religious sites. This highlights the critical role of Ecosystem Services in local livelihoods and underscores the need for integrated management approaches. The study suggested that the next studies may relate to the economic value of provisioning and Cultural Ecosystem Service, examining land use and land cover change, and so far, assessing the link between local traditional ecological understanding and Ecosystem Services.